Organizational Citizenship Behavior Employment Gas Station in Indonesia (Literature Review) - Istiqomah, Anisa; Aminalul , Safira; Rizana, Dani (SMARTINDO, 2024)
Organizational citizenship behavior (OCB) is very important for Public Fuel Filling Station (SPBU) employees because of the increasing demand for fuel. Even causing long queues at gas stations. This often happens in the morning and evening. According to data from the Central Statistics Agency (BPS), the transportation and storage sector shows stable growth. In this context, OCB is becoming increasingly important for gas station employees to maintain competitiveness and improve service quality at gas stations. Gas stations operate in a highly competitive environment, where customer satisfaction is the key to success. OCB can increase gas station customer satisfaction. Staff who are agile in helping customers and supporting co-workers can reduce wait times and improve the customer experience. This implies higher customer loyalty, which is very important in a competitive industry. Employees who demonstrate OCB can improve the customer experience by providing better and more responsive service. The results of the analysis state that Organizational Citizenship Behavior (OCB) plays a crucial role in increasing customer satisfaction, organizational performance and the competitiveness of gas stations in Indonesia. To encourage OCB, HR management needs to create a supportive environment with effective reward strategies, good leadership and appropriate training programs. However, challenges such as high employee rotation and limited resources remain obstacles that must be overcome.